Fearless Facilitation - Maxey, Cyndi; O'Connor, Kevin (Ascent Audio, 2020)
This book will help the reader plan every meeting with AUDIENCE MINDSET top of mind, begin every meeting with an IMMEDIATELY INVOLVING ACTIVITY or discussion that unifies the group, locate the KEY POINTS in the meeting to FACILITATE and INVOLVE, rather than lecture and present information, USE EASY-TO-IMPLEMENT facilitative techniques with ANY TYPE OF PARTICIPANT (job roles, levels, backgrounds, gender, culture, attitude, and FOLLOW UP to every intervention with clarity and speed. TABLE OF CONTENTS I. HEARD ON THE STREETS (and from their seats) Why todays meetings are so bad and what to do about it. Why involve? Why ask? Who cares? The psychology and group-ology of involvement; the benefits of skilled facilitation for todays meeting and for todays leader. II. ORGANIC FACILITATION How to be comfortable with this new skill, how to make it look easy, and how to be useful to the audience. Like organic food, its less known, healthier, and takes time to perfect, but it is the result that makes it most valuable. III. THE FOURTH WALL To borrow from a theatrical term, allowing the fourth wall (that invisible wall that separates the audience from the actors). This wall also exists between presenters and their audiences unless it is opened up through dialogue, doing so early and often, and setting up the entire meeting for success. IV. HAVE FUN ONE BY ONE AND ONE HUNDREDUsing the experts and the expertise among you to achieve more than before. Include and connect and you will engage memory and action for results unheard of in ordinary meetings. V. DIALOGUE NOT MONOLOGUE (or worse, DUALOGUE) The accent is on how conversation and facilitation skills intertwine, how to keep our largely introverted professional population involved in the conversation of the meeting purpose, and, of course, what to do when they do talk, contribute, and even argue. VI. THE SET UP How to set up discussion topics and activities gently, so people really do them instead of complaining or going silent! What groups of 6 and 600 have in common when it comes to getting involved with you. Every member of your audience and team is a value interpreter and as such they are the sole experts on your meeting skills and are the ones to take the message and do something with itor not! VII. LISTEN LIVE - How to borrow from the b...